2020
DOI: 10.3390/nano10020400
|View full text |Cite
|
Sign up to set email alerts
|

Safe Administration of Carbon Nanotubes by Intravenous Pathway in BALB/c Mice

Abstract: Carbon nanotubes (CNTs) are nanomaterials with multiple possible uses as drug carriers or in nanovaccine development. However, the toxicity of CNTs administered intravenously in in vivo models has not been fully described to date. This work aimed to evaluate the toxic effect of pristine multi-walled CNTs (UP-CNTs), purified (P-CNTs), or CNTs functionalized with fluorescein isothiocyanate (FITC-CNTs) administered by intravenous injection in BALB/c mice. Biochemical and histopathological parameters were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…31 Guzmán-Mendoza et al reported functionalization-dependent toxicity of MWCNTs after intravenous injection of mice with 2 mg/kg bodyweight NMs. 32 Therefore, the concentration of MWCNTs used in this study is comparable to previous studies. For HNTs, relatively few studies investigated the toxicity of HNTs after intravenous injection, but some studies investigated the toxicity HNTs to mice via other exposure routes.…”
Section: Intravenous Injection For Micesupporting
confidence: 77%
“…31 Guzmán-Mendoza et al reported functionalization-dependent toxicity of MWCNTs after intravenous injection of mice with 2 mg/kg bodyweight NMs. 32 Therefore, the concentration of MWCNTs used in this study is comparable to previous studies. For HNTs, relatively few studies investigated the toxicity of HNTs after intravenous injection, but some studies investigated the toxicity HNTs to mice via other exposure routes.…”
Section: Intravenous Injection For Micesupporting
confidence: 77%
“…MWCNTs were administrated intravenously, and biochemical and histopathological parameters were analyzed at 1, 14, 29, and 60 days post-exposure. Pristine MWCNTs have shown the highest toxicity, especially due to accumulation in the kidneys and the lungs even at 60 days [ 93 ]. Tang et al studied short-term and long-term toxicity of multi-walled carbon nanotubes.…”
Section: Nephrotoxicitymentioning
confidence: 99%
“… 131 Synthesis methods that focus on the preparation of CNTs with better physicochemical properties are needed to accomplish this. 132 Also, the compatibility of CNTs can be improved by creating oxidized tubes that exhibit enhanced biodegradative potential and limited biopersistence.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%